2014
DOI: 10.1523/jneurosci.1081-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Area MT Encodes Three-Dimensional Motion

Abstract: We use visual information to determine our dynamic relationship with other objects in a three-dimensional (3D) world. Despite decades of work on visual motion processing, it remains unclear how 3D directions-trajectories that include motion toward or away from the observer-are represented and processed in visual cortex. Area MT is heavily implicated in processing visual motion and depth, yet previous work has found little evidence for 3D direction sensitivity per se. Here we use a rich ensemble of binocular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 65 publications
3
74
0
Order By: Relevance
“…Applying their protocol will require incorporating sensitivity to changing disparity into our model framework. Disparity studies may provide additional constraints on sources of opponent inhibition, as disparity-tuned motion-opponent suppression has been described in studies of transparent motion in MT (Qian and Andersen, 1994;Bradley et al, 1995). Opponent suppression may be mediated by reciprocal interactions between disparity channels in MT or from interactions between disparity-tuned V1 subunit inputs to MT, as proposed in models of IOVD processing (Sabatini and Solari, 2004).…”
Section: Accounting For Disparity Selectivity In Mtmentioning
confidence: 97%
See 3 more Smart Citations
“…Applying their protocol will require incorporating sensitivity to changing disparity into our model framework. Disparity studies may provide additional constraints on sources of opponent inhibition, as disparity-tuned motion-opponent suppression has been described in studies of transparent motion in MT (Qian and Andersen, 1994;Bradley et al, 1995). Opponent suppression may be mediated by reciprocal interactions between disparity channels in MT or from interactions between disparity-tuned V1 subunit inputs to MT, as proposed in models of IOVD processing (Sabatini and Solari, 2004).…”
Section: Accounting For Disparity Selectivity In Mtmentioning
confidence: 97%
“…1A), we chose a simple and robust model of direction selectivity based on the motion energy model (Adelson and Bergen, 1985). Our V1 computation consists of the following steps for each direction channel: (1) convolving the stimulus, a sequence of images over time, with two spacetime oriented Gabor filters in quadrature; (2) squaring and summing the outputs to produce a directional motion energy signal; and (3) half-wave rectifying this opponent motion energy signal to produce a non-negative response.…”
Section: V1 Direction Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two independent and complementary studies recently examined this issue. Czuba et al (2014) found that the majority of neurons in MT (70%) encode information about 3D direction of motion on the basis of binocular cues. Approximately one-third of those (17% of the total) preferred motion trajectories directly toward or away from the observer (note that this is actually a neural overrepresentation because, at most reasonable viewing distances, the distance between the eyes subtends far less than 17% of the horizontal visual field).…”
Section: Brain Mechanisms For 3d Motion Informationmentioning
confidence: 99%